Comparison of Pentaerythrotol and Its Derivatives as Intumescent Flame Retardants for Polypropylene. (28th August 2018) - Huang, Siwen; Xu, Jiayou; Deng, Haiming; Liu, Jie; Xiao, Yuanfang
Abstract : Hydroquinol bis[di(2, 6, 7-trioxa-phosphabicyclo[2.2.2]-octane-1-oxo-4-hydroxylmethyl)]phosphate (PBPP), which contains caged phosphates and benzene groups, was synthesized. The caged phosphate structure of PBPP was characterized by Fourier transform infrared spectroscopy (FT-IR), hydrogen nuclear magnetic resonance ( 1 H-NMR), and phosphorus nuclear magnetic resonance ( 31 P-NMR). The experimental results showed that PBPP had better performance than 1-oxo-4-hydroxymethy1-2, 6, 7-trioxa-1-phosphabicyclo[2.2.2]-octane (PEPA) and pentaerythritol (PER) in water resistance, compatibility with polypropylene (PP), thermal stability, and flame retardancy of intumescent flame retardant PP (IFR-PP) systems. It was attributed to the symmetrical structure and stereohindrance effect of PBPP. The IFR-PP systems reached UL94 V-0 flammability rating when the minimal addition of IFR with PBPP, PEPA, or PER was 25%, 23%, and 28%, respectively. The flame retardant mechanisms of IFR containing PBPP, PEPA, and PER were investigated by FT-IR and scanning electron microscopy (SEM). PBPP formed a perfect charring layer, with the high carbon content of PBPP helping it form the charring layer more quickly.